Elevating Efficiency: Designing an Integrated E-commerce Platform for Atlanta Sport Store Based on Yii Framework - Eltiana, Nia Irma; Saputra, Hadi Kurnia (Sagamedia Teknologi Nusantara, 2024)
E-commerce has become a dominant trend in buying and selling transactions; however, the Atlanta Sport Store still relies on a manual approach to managing data, marketing, product sales, and generating sales reports. To address this challenge, we propose an innovative e-commerce platform design for the Atlanta Sport Store. The development methodology involved the waterfall method and Unified Modeling Language (UML) modeling. The programming stack includes PHP as the programming language, MySQL as the database management system (DBMS), and XAMPP as the web server, with coding performed through browsers such as Google Chrome. The primary objective of this design is to create an effective e-commerce site, facilitating customers to find information and make product purchase transactions while simplifying store management activities. This e-commerce design not only addresses online sales needs but also optimizes inventory management, transaction reporting, and financial reporting for store owners. This study makes a significant contribution to optimizing business operations through the implementation of an integrated e-commerce solution, opening up opportunities for increased efficiency and competitiveness in the retail sector.